The prevalence of factor VIII inhibitor in patients with severe hemophilia-A and its clinical characteristics - Harijadi Harijadi; Djajadiman Gatot; Arwin AP Akib (Paediatrica Indonesiana, 2005)
Background Hemophilia is a hereditary blood-clotting disorderdue to factor VIII deficiency. Up to this date, the administration offactor VIII in preventing and managing bleeding has been the maintreatment. One of the complications, which may occur due to re-peated administrations of factor VIII, is the formation of factor VIIIantibody (factor VIII inhibitor).Objective To find out the prevalence of severe hemophilia-A withfactor VIII inhibitor and its clinical characteristics.Methods A cross-sectional descriptive study was performed onchildren with severe hemophilia-A at the National Hemophilia CareCentre, Cipto Mangunkusumo Hospital, Jakarta, Indonesia, in June-August 2004.Results Out of 45 children studied, 16 had factor VIII inhibitor withaverage inhibitor titre of 1.15 Bethesda units (BU) (range 0.15-15BU). Most of them (12 patients) had inhibitor titre <5 BU. Chronicarthropathy was found in 17 out of 45 (37%) children with severehemophilia-A, consisting of nine patients from positive inhibitorgroup and 8 patients from negative inhibitor group. Thirty-ninepatients (86%) used an on-demand treatment pattern, among whom15 had positive inhibitor. Among patients receiving prophylactictreatment pattern, only one had positive inhibitor. There were 39patients (86%) treated using cryoprecipitate, among whom factorVIII inhibitor was found in 12, while among those treated with fac-tor VIII concentrate, the inhibitor was positive in 4/6. The averageamount of factor VIII transfused in positive and negative factor VIIIinhibitor groups was similar.Conclusion The prevalence of factor VIII inhibitor in severe he-mophilia-A patients was 35%. Chronic arthropathy occurred moreoften in patients with positive factor VIII inhibitor. Factor VIII inhibi-tor was found more frequently in patients with an on-demand treat-ment pattern and in those using factor VIII concentrate